Recent Advances in Extracellular Vesicles as Drug Delivery Systems and Their Potential in Precision Medicine - Bart de Jong; Eric Raul Barros; Joost G. J. Hoenderop; Juan Pablo Rigalli (MDPI AG, 2020)
Extracellular vesicles (EVs) are membrane-bilayered nanoparticles released by most cell types. Recently, an enormous number of studies have been published on the potential of EVs as carriers of therapeutic agents. In contrast to systems such as liposomes, EVs exhibit less immunogenicity and higher engineering potential. Here, we review the most relevant publications addressing the potential and use of EVs as a drug delivery system (DDS). The information is divided based on the key steps for designing an EV-mediated delivery strategy. We discuss possible sources and isolation methods of EVs. We address the administration routes that have been tested in vivo and the tissue distribution observed. We describe the current knowledge on EV clearance, a significant challenge towards enhancing bioavailability. Also, EV-engineering approaches are described as alternatives to improve tissue and cell-specificity. Finally, a summary of the ongoing clinical trials is performed. Although the application of EVs in the clinical practice is still at an early stage, a high number of studies in animals support their potential as DDS. Thus, better treatment options could be designed to precisely increase target specificity and therapeutic efficacy while reducing off-target effects and toxicity according to the individual requirements of each patient.